CHALLENGES IN LITERARY TRANSLATION: A CASE IN ENGLISH-VIETNAMESE TRANSLATION OF“THE GREAT GATSBY” - Hang, Trieu Thu (VNU Journal of Foreign Studies, 2022)
The present study aims to analyze challenges that the translator confronts in the English-Vietnamese translation of “The Great Gatsby”. The major method adopted in the study is comparative descriptive approach, which enables the researcher to describe the difficulties in the English-Vietnamese translation of “The Great Gatsby”. The findings unravel a number of constraints associated with linguistic and cultural differences between the source and the target language. Several recommendations to overcome the hindrances are also proposed.